Environmental effects on turfgrass growth and water use - Peterson, Kenton W. (Kansas State University, 2013)
Researchers and practitioners can use numerous techniques to measure or estimate evapotranspiration (ET) from turfgrass but little is known about how they compare to ET using standard lysimeters. An investigation was conducted to compare measurements of ET from lysimeters (LYS[subscript]E[subscript]T) with ET estimates from the FAO56 Penman-Monteith (PM[subscript]E[subscript]T) and Priestley-Taylor (PT[subscript]E[subscript]T) empirical models, atmometers (AT[subscript]E[subscript]T), eddy covariance (EC[subscript]E[subscript]T), and a canopy stomatal conductance model that estimates transpiration (COND[subscript]T). Methods were compared at the same site during the 2010, 2011, and 2012 growing seasons. Overall, PT[subscript]E[subscript]T and EC[subscript]E[subscript]T were not different from LYS[subscript]E[subscript]T, whereas PM[subscript]E[subscript]T, AT[subscript]E[subscript]T, and COND[subscript]T, increasingly underestimated LYS[subscript]E[subscript]T. Differences exist among ET measurement techniques and one should employ the technique that best fits their situation. An atmometer is an inexpensive tool that can be used to measure turfgrass ET within microclimates, such as those typically found in an urban home lawn. An investigation was conducted to compare AT[subscript]E[subscript]T estimates with PM[subscript]E[subscript]T estimates within a number of lawn microclimates. Home lawns in Manhattan and Wichita, KS, were selected for study during the growing seasons of 2010 and 2011. Open sward AT[subscript]E[subscript]T was 4.73 mm d[superscript]-[superscript]1, whereas PM[subscript]E[subscript]T was 5.48 mm d[superscript]-[superscript]1. Within microclimates, AT[subscript]E[subscript]T was 3.94 mm d[superscript]-[superscript]1 and PM[subscript]E[subscript]T 3.23 mm d[superscript]-[superscript]1. Atmometers can provide practitioners with reliable estimates of PM[subscript]E[subscript]T within microclimates. Zoysiagrass (Zoysia spp.) is a common turfgrass used on home lawns and golf courses. However, poor shade tolerance and cold hardiness have limited its use in the transition zone. A study was conducted to determine changes and differences in growth and physiology among selected Zoysia over a three-year period (2010-2012) in the transition zone. The genotypes were 'Emerald' [Z. japonica × Z. pacifica], 'Zorro' [Z. matrella], 'Meyer' and Chinese Common [Z. japonica], and experimental progeny Exp1 [Z. matrella × Z. japonica], and Exp2 and Exp3 [(Z. japonica × Z. pacifica) × Z. japonica]. 'Zorro' and 'Emerald' experienced winter injury. 'Meyer', Chinese Common, and Exp1 showed poor performance over the three-years. The Exp2 and Exp3 progeny, maintained high percent cover, visual quality, and tiller density, and may provide practitioners more shade-tolerant cultivar choices in the transition zone.
Keywords: Evapotranspiration; Shade; Grass; Agronomy (0285); Biology, Plant Physiology (0817); Horticulture (0471)